Nilai Kepemimpinan dalam Cerita Rakyat Panglima Wangkang di Marabahan sebagai Cerminan Kearifan Lokal Masyarakat Banjar - Siti Hadijah; Rizkina Zahra; Zahra Anisa; Dwi Wahyu Candra Dewi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study discusses the leadership values reflected in the folklore of Panglima Wangkang in Marabahan as a representation of the local wisdom of the Banjar-Bakumpai community. Panglima Wangkang is recognized as a prominent figure who played a significant role in resisting Dutch colonialism in the Barito region. This research aims to examine Panglima Wangkang not only as a war hero but also as a symbol of cultural unity, religious values, and traditional leadership that still lives in the collective memory of society today. The study employs a qualitative historical method with a postcolonial approach. The data were collected through library research involving historical archives, scientific journals, books, and documented folklore. The research stages included heuristics, source criticism, interpretation, and historiography. The findings reveal that Panglima Wangkang’s leadership reflects the values of courage, strategic intelligence, loyalty, religiosity, and social concern. His well-known military strategy, referred to as the “Trojan Horse” technique, demonstrates his tactical ability in confronting colonial forces. In addition, religious values are reflected in his message to always maintain ablution and in the belief regarding martyrdom. The story of the golden bullet also symbolizes the community’s respect for the struggle and honor of local heroes. Panglima Wangkang’s cross-ethnic identity as both Banjar and Bakumpai further strengthened community unity in facing colonialism. This study shows that folklore functions not only as a cultural heritage but also as a medium for transmitting leadership values and local identity that remain relevant in the social life of the Marabahan community today.